The Effect of Organizational Culture and Supplier Integration to Supply Chain Performance - Laulita, Nasar Buntu (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2020)
This study aims to investigate the influence of four types of organizational cultures and supplier integration to supply chain performance. The methodology of this research is an explanatory study by testing two hypotheses. The dataâ€™s were collected from a convenience samples of 171 manufacturing companies of total 850 companies in Kepulauan Riau Province being represented by manager in supply chain management divisions. Dataâ€™s were collected using questionnaire and technical data analysis using SEM (Structural Equation Model). The result of this study found that: (1) Group Culture and Rational Culture affect Supply Chain Performance positively and significantlyÂ but Development Culture and Hierarchical Culture are not significant; (2) Supplier Integration affects Supply Chain Performance positively and significantly. The managerial implication of this research is as a guidance for decision maker in the company or manager in the supply chain management to implement suitable organizational culture and consider the supplier integration as a strategic to improve Supply Chain Performance.